Consumers' perception of automatic emergency braking (AEB): Theoretical model and construct development - Mohd Ishanuddin, N.; Sukadarin, Ezrin Hani; Mohd Nawi, N. S.; Widia, Mirta; Ab Rashid, A. A.; H. A., Aziz; Junaidah, Zakaria; Fauzan, N. S.; Osman, H.; Roslin, E. N.; Jawi, Z. M.; Yassierli, . (Society of Automotive Engineers Malaysia, 2021)
Due to remarkable developments, various automated driving systems, known as Advanced Driver Assistance Systems (ADAS), have been implemented, and the entire range of human driver activity in modern vehicles is undergoing changes. However, whether or not the consumers will accept and satisfy the emerging technologies, especially Automatic Emergency Braking (AEB), remains a big question. Therefore, it is vital to understand how vehicle consumers or potential consumers decide to use or not to use, and what they expect or perceive of AEB. This work intends to review the published works on AEB to understand the current market of the technology. In order to investigate the user's perception, a developed theoretical model is planned to be adopted. The review was conducted by searching from Google Scholar and the ScienceDirect database through Universiti Malaysia Pahang online databases. The knowledge and understanding of the current AEB market and theoretical model will help researchers plan the next steps to explore consumer or potential consumer perception.